1983
DOI: 10.1159/000172882
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Glomeruli in the Renal Cortex of Munich Wistar Frömter (MWF) Rats

Abstract: The glomerular distribution in the renal cortex of the Munich Wistar Frömter (MWF) rat, a substrain of the Munich Wistar rat selected for superficial glomeruli, was compared to that of a control strain (LEW/Ztm) between 10 and 150 days of age. While there were no significant differences in body growth, kidney weight, or growth of the renal cortex in these two strains, the average diameter of Bowman’s capsule and of the glomerular tuft was significantly larger (about 12%) in rats of the MWF strain which were ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…128,129 The colony MWF/ FUB renamed as MWF/ Rkb and more recently to MWF/FubRkb was established in 1996 by further inbreeding of rats from the original colony at the Charité -Universitätsmedizin Berlin, Germany. 130 Strain characteristics MWF rats develop mild SS spontaneous hypertension, spontaneous albuminuria of early onset, structural renal abnormalities such as an inherited nephron reduction of 30-50%, glomerulosclerosis, reduced podocyte number, renal interstitial fibrosis and endothelial dysfunction.…”
Section: Munich Wistar Frö Mter Rat Strain Breedingmentioning
confidence: 99%
“…128,129 The colony MWF/ FUB renamed as MWF/ Rkb and more recently to MWF/FubRkb was established in 1996 by further inbreeding of rats from the original colony at the Charité -Universitätsmedizin Berlin, Germany. 130 Strain characteristics MWF rats develop mild SS spontaneous hypertension, spontaneous albuminuria of early onset, structural renal abnormalities such as an inherited nephron reduction of 30-50%, glomerulosclerosis, reduced podocyte number, renal interstitial fibrosis and endothelial dysfunction.…”
Section: Munich Wistar Frö Mter Rat Strain Breedingmentioning
confidence: 99%
“…The glomerulosclerosis index (GSI) was assessed using a semiquantitative scoring system as previously reported, analyzing both superficial and juxtamedullary glomeruli (14 15). Two phenotypes for the presence of superficial glomeruli were determined: first, the number of surface glomeruli per section with direct contact to the surface was counted; second, all superficial glomeruli present in the renal cortex corticis zone but without direct surface contact were counted in three mid-coronal sections for each animal, respectively (16). The mean values were calculated and taken for linkage analysis.…”
Section: Phenotypingmentioning
confidence: 99%
“…The advantage of using this strain is that most glomeruli are located under the vicinal surface of the kidney, and with this glomerular localization, the glomerular vessels and fluid from the Bowman's capsule are directly acces sible (12,13). Therefore, extensive pharmacological and physiological studies of glomerular characteristics have been carried out with this strain (30)(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, extensive pharmacological and physiological studies of glomerular characteristics have been carried out with this strain (30)(31)(32)(33)(34)(35)(36). With respect to the localization of glomeruli, Hackbarth et al (12) report ed that an average of 3-4 superficial glomeruli was ob served in each histological section in MW rats aged be tween 20 and 100 days, while in the control rat kidney, only 2 superficial glomeruli were found in all histological sections. They also reported that at ages of over 100 days, the number of superficial glomeruli diminished to about one per section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation